Effect of Essential Oil Applications on Sugar Beet (Beta vulgaris L.) Root Quality During Storage - Fatma Zehra Ok; Arif Şanlı; Yeşim Cirit; Bekir Tosun (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in order to determine the effects of dill, clove and hyssop essential oils and fungicides applied on sugar beet roots on beet storage quality during the storage period. The roots of Esperanza (KWS) variety, which was produced in the experimental areas in 2019, were used in the study. Roots were treated with 100, 500 and 1000 ppm doses of dill (Anethum graveolens L.), clove (Szygium aromaticum) and hyssop (Echinophora tenuifolia) essential oils, synthetic fungicide (80% Thiram) and Tween-80 right after harvest and the roots were placed in the storage. Weight loss of roots determined at 15-day intervals from the beginning of the storage period, dry matter ratio, brix, polar sugar, reducing sugar and alpha amino nitrogen contents, phytotoxicity and fungal infection development at the end of the 3-month storage period. The applications made in the research significantly affected the post-harvest weight and quality losses in beet. Depending on the applications, the weight losses at the end of the 3-month storage period varied between 9.43-19.90%, and the weight losses in essential oil applications were lower than the control. The highest dry matter content and brix values were obtained from clove essential oil and fungicide and Tween-80 applications. While Tween-80 and fungicide applications increased the polar sugar content compared to the control, 1000 ppm clove essential oil caused a significant decrease in the polar sugar content. In the study, reducing sugar and alpha amino nitrogen contents of roots applied 1000 ppm essential oil E. tenuifolia essential oil were lower. E. tenuifolia essential oil showed the highest antifungal activity against white mold and green mold infections. It was concluded that with the application of essential oil to the roots after the harvest, both weight and quality losses and the development of fungal diseases can be reduced, however, some active substances may cause phytotoxicity in the roots.